Peningkatan Perilaku Hand Hygiene Enam Langkah untuk Pencegahan Penyakit Menular di Fasilitas Kesehatan - Niswatul Inayah; Syahda Fhauliah Putri, Anabela Sidik; Difa Razki, Nazwa Auliya Chaerunnisa; Mufidah Khoiriyyah, Alia Resti Andri Putri, Yunita Avita Ayu Nasution; Nawra Fazila, Azzahra Cinta Ramadhini (Yayasan Daarul Huda Kruengmane, 2025)
Healthcare-Associated Infections (HAIs) remain a serious problem that requires immediate attention, due to low handwashing compliance. The World Health Organization (WHO, 2023) reports that hand hygiene compliance remains low, averaging only around 40% worldwide, and can be as low as 2% in low-income countries. In Indonesia, Ministry of Health data shows an incidence rate of 15.74%, while a survey of 10 teaching hospitals reported an average of 9.8%. Interventions in the form of hand hygiene education or training have proven effective in increasing knowledge and compliance among both patients and healthcare workers. In line with this, the community service activity was themed